2022
DOI: 10.1097/acm.0000000000004597
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic Solidarity or Virtue Signaling? A Critical Discourse Analysis of the Public Statements Released by Academic Medical Organizations in the Wake of the Killing of George Floyd

Abstract: Purpose Many academic medical organizations issued statements in response to demand for collective action against racial injustices and police brutality following the murder of George Floyd in May 2020. These statements may offer insight into how medical schools and national organizations were reflecting on and responding to these incidents. The authors sought to empirically examine the initial statements published by academic medical organizations in response to societal concerns about systemic, anti-Black ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…However, in an analysis of 45 such statements, researchers found that one third did not include the words “racism” or “racist.” Of those that did, many minimized institutional accountability by focusing on interpersonal racism, and offered no commitments to specific actions. In addition, many used the words “diversity, equity, and inclusion,” or highlighted past DEI work unrelated to racial justice, rather than explicitly address anti-Black racism ( 36 ). In other words, following a clear national moment of racial reckoning, academic medical institutions were unable or unwilling to name racism, failed to acknowledge medicine's role in perpetuating racial violence and structural inequities, and instead often conflated DEI work with anti-racism.…”
Section: Introductionmentioning
confidence: 99%
“…However, in an analysis of 45 such statements, researchers found that one third did not include the words “racism” or “racist.” Of those that did, many minimized institutional accountability by focusing on interpersonal racism, and offered no commitments to specific actions. In addition, many used the words “diversity, equity, and inclusion,” or highlighted past DEI work unrelated to racial justice, rather than explicitly address anti-Black racism ( 36 ). In other words, following a clear national moment of racial reckoning, academic medical institutions were unable or unwilling to name racism, failed to acknowledge medicine's role in perpetuating racial violence and structural inequities, and instead often conflated DEI work with anti-racism.…”
Section: Introductionmentioning
confidence: 99%
“…7 Many academic medical organizations released statements in response to concerns about systemic racism in the aftermath of George Floyd's death and made incremental changes in policy. 8 Yet little research has examined the impact of social unrest due to systemic racism on early-career scientists from UR backgrounds. Research from the National Institutes of Health shows that civil unrest tied to racism negatively impacted approximately half of extramural researchers who identified as women, Black or African American, or Hispanic.…”
Section: Introductionmentioning
confidence: 99%
“…Many academic medical organizations released statements in response to concerns about systemic racism in the aftermath of George Floyd's death and made incremental changes in policy [8]. Yet little research has examined the impact of social unrest due to systemic racism on early-career scientists from UR backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…The recent public commitments to anti‐racism and anti‐oppression work made by many medical schools and universities in response to the Black Lives Matter movement 10 provide impetus to examine the structures, programmes and policies that harm and discriminate against marginalised medical students. Critical policy analysis methods have been used to understand how medical school accreditation and educational standards exclude medical students with disabilities 11 .…”
Section: Introductionmentioning
confidence: 99%
“…6 The prototypical example is the policing of Black women's natural hair as unprofessional, 7,8 thus placing pressure on Black women to process or change their hair to conform to a more socalled professional, Eurocentric appearance. 9 The recent public commitments to anti-racism and antioppression work made by many medical schools and universities in response to the Black Lives Matter movement 10 provide impetus to examine the structures, programmes and policies that harm and discriminate against marginalised medical students. Critical policy analysis methods have been used to understand how medical school accreditation and educational standards exclude medical students with disabilities.…”
Section: Introductionmentioning
confidence: 99%